The acute effects of compression garments on muscle protein synthesis markers, blood flow, performance, and perceived recovery after resistance exercise - Leabeater, A. J.; Broatch, J. R.; Driller, M. W.; James, L. P.; Malamouli, M.; Halson, S. L.; Bishop, D. J.; Garnham, A.; O`Riordan, S. F. (Medicine & Science in Sports & Exercise, 2025)
Introduction/Purpose Compression garments are a commonly used recovery aid following resistance exercise, which may improve muscle blood flow and perceived recovery. However, there has been limited insight into the underlying molecular mechanisms that may mediate the physiological effects of compression garments. The aim of this study was to investigate the effect of compression tights on markers of muscle protein synthesis, muscle blood flow, and indices of recovery following a bout of resistance exercise.